An assessment of the Education Management Information System in Sierra Leone and potential for enhanced disability inclusiveness - Steven Kaindaneh; Julia de Kadt; Stevens Bechange; Emma Jolley; Nancy Smart; Elena Schmidt (International Journal of Educational Research Open)
Millions of children live with disabilities worldwide and many of them are at risk of being excluded from education, particularly in low- and middle-income countries (LMICs). For children with disabilities enrolled in schools, learning outcomes and completion rates are often lower compared to that of their peers without disabilities. The effective and equitable access to education for all requires robust education data systems to monitor potential inequalities. For this purpose, Education Management Information Systems (EMIS) have been deployed, with varying degrees of effectiveness. In Sierra Leone, EMIS was established in 2006 but the evidence on its effectiveness and inclusiveness remains limited. This study aimed to examine the strengths and weaknesses of the current EMIS and determine how it can be made more disability inclusive. Guided by the System Approach for Better Education Results (SABER) EMIS framework, the study collected data through a documentary review, interviews and focus group discussions with purposively selected education stakeholders. The study revealed that EMIS in Sierra Leone is at the emerging stage of development and while it is a major government priority, there are several weaknesses that need to be addressed in order to maximise its overall performance. At present, EMIS equates to the annual school census; it presents data on a number of indicators, including disability status, but only in the aggregate format. EMIS does not contain any individual student data making educational planning challenging. The study provides a number of recommendations for system strengthening.